Exploring Differentiated Learning: A Bibliometric Examination of Research Development and Directions - Thayibah, Khamsah Ruhana; Salim, Hakimmuddin; Shohib, Muhammad Wildan; Maksum, Muh. Nur Rochim; Apriantoro, Muhamad Subhi (Universitas Muhammadiyah Surakarta, 2023)
Purpose: To chart the progress and trajectory of differentiated learning research in Scopus database-indexed publications from 1954 - 2023. The first publication was found in 1994. Methodology: Using bibliometric analysis method. A literature review was performed to ensure that relevant research on bibliometric topics was conducted. A Boolean search engine was utilized to search the Scopus database from 1954 to 2023. The analysis of citations, document content, and networks was carried out using R and Rstudio tools, VosViewer, and Microsoft Excel. Using the Boolean operator TITLE-ABS-KEY (differentiated and learning) to search Scopus and generate 7,012 documents. Filtering is done with the Boolean operator (LIMIT-TO (SUBJAREA,